Practice of using gifts as promotional materials for marketing of pharmaceutical products in Bangladesh: a survey conducted on general physicians and representatives from pharmaceutical companies - Sultana, Saki; Khosru, Kamrul Hasan (© 2011 Stamford Journal of Pharmaceutical Sciences, 2016)
This article was published in Stamford Journal of Pharmaceutical Sciences [© 2011 Stamford Journal of Pharmaceutical Sciences] and the definite version is available at : http://www.banglajol.info/index.php/SJPS/article/view/10434/7712 The article website is at: http://www.banglajol.info/index.php/SJPS